Heterogeneous Vascular Bed Responses to Pulmonary Titanium Dioxide Nanoparticle Exposure - Abukabda, Alaeddin B.; Stapleton, Phoebe A.; McBride, Carroll R.; Yi, Jinghai; Nurkiewicz, Timothy R. (Frontiers in Cardiovascular Medicine, 2017)
A growing body of research links engineered nanomaterial (ENM) exposure to adverse cardiovascular endpoints. The purpose of this study was to evaluate the impact of ENM exposure on vascular reactivity in discrete segments so that we may determine the most sensitive levels of the vasculature where these negative cardiovascular effects are manifest. We hypothesized that acute nano-TiO2 exposure differentially affects reactivity with a more robust impairment in the microcirculation. Sprague-Dawley rats (8–10 weeks) were exposed to nano-TiO2via intratracheal instillation (20, 100, or 200 µg suspended per 250 µL of vehicle) 24 h prior to vascular assessments. A serial assessment across distinct compartments of the vascular tree was then conducted. Wire myography was used to evaluate macrovascular active tension generation specifically in the thoracic aorta, the femoral artery, and third-order mesenteric arterioles. Pressure myography was used to determine vascular reactivity in fourth- and fifth-order mesenteric arterioles. Vessels were treated with phenylephrine, acetylcholine (ACh), and sodium nitroprusside. Nano-TiO2 exposure decreased endothelium-dependent relaxation in the thoracic aorta and femoral arteries assessed via ACh by 53.96 ± 11.6 and 25.08 ± 6.36%, respectively. Relaxation of third-order mesenteric arterioles was impaired by 100 and 20 µg nano-TiO2 exposures with mean reductions of 50.12 ± 8.7 and 68.28 ± 8.7%. Cholinergic reactivity of fourth- and fifth-order mesenteric arterioles was negatively affected by nano-TiO2 with diminished dilations of 82.86 ± 12.6% after exposure to 200 µg nano-TiO2, 42.6 ± 12.6% after 100 µg nano-TiO2, and 49.4 ± 12.6% after 20 µg nano-TiO2. Endothelium-independent relaxation was impaired in the thoracic aorta by 34.05 ± 25% induced by exposure to 200 µg nano-TiO2 and a reduction in response of 49.31 ± 25% caused by 100 µg nano-TiO2. Femoral artery response was reduced by 18 ± 5%, while third-order mesenteric arterioles were negatively affected by 20 µg nano-TiO2 with a mean decrease in response of 38.37 ± 10%. This is the first study to directly compare the differential effect of ENM exposure on discrete anatomical segments of the vascular tree. Pulmonary ENM exposure produced macrovascular and microvascular dysfunction resulting in impaired responses to endothelium-dependent, endothelium-independent, and adrenergic agonists with a more robust dysfunction at the microvascular level. These results provide additional evidence of an endothelium-dependent and endothelium-independent impairment in vascular reactivity.